The feasibility of the PicPecc application as an mHealth tool: Reflections from South African children - Ensa Johnson; Khetsiwe Masuku; Stefan Nilsson; Juan Bornman; Arine Kuyler (Rehabilitation Advances in Developing Health Systems)
Background: Access to technology (and data) through mobile health (mHealth) can alleviate some of the challenges children experience in accessing healthcare services. However, the South African context is unique with children living in under-resourced and rural communities, with limited transport, long commute times to reach clinics, and poor access to technology. Therefore, even though mHealth tools can be beneficial, researchers need to determine the feasibility of such an application for the South African context.